Psychologists' practices in child custody evaluations: guidelines, psychological testing and the ultimate opinion rule - Thompson, Glyde Edward (University of the Free State, 2012)
This study examined 24 child custody reports on the basis of seven evaluation guidelines compiled from international and South African literature. The purpose of the research was to determine the extent to which psychologists performing custody evaluations followed these or similar guidelines as methodological points of departure in their assessment process. Although the results in general indicated an adherence to some of the guidelines, the following concerns were noted: a) Several of the psychologists did not utilise multiple methods of data gathering. b) Some of the psychologists performed custody evaluations without considering the important variables of parenting capacity, the needs of the child and the resulting fit. c) A number of psychologists made custody recommendations without assessing both parents and the children. d) Assessment of the child’s wish was almost completely absent. These shortcomings indicate a need for better training of child custody evaluators, as well as the need for a comprehensive protocol of practice guidelines for South African psychologists working in this field. Limitations of the study are indicated and guidelines are provided for psychologists performing child custody evaluations. The use of psychological tests in custody evaluations is controversial. While some authors endorse their use, others express a guarded use, and still others strongly advocate against their use. The most common reason for this controversy involves the contention that standard psychological tests are not designed and standardised to directly assess the legal issue of the best interest of the child or parenting capacity, while the general reliability and validity of most tests are also at issue. This study examined 24 child custody reports of psychologists that were utilised by the Office of the Family Advocate in Cape Town and Port Elizabeth. A content analysis of each psychologist’s report was performed to determine their testing practices. Children were assessed with psychological tests in 72% and parents in 67% of cases. Structured personality tests were used mostly with the parents and projective tests mostly with the children. Some concerns emerged regarding the practices of these psychologists: in the majority of cases, the tests used were not standardised for the South African population, or outdated and/or inappropriate to address the legal issue. The majority did not indicate any form of limitation regarding the psychological tests used, nor were any validation research indicated for the use of foreign tests in the South African context. These practices pose a danger to the judicial process and indicate a need for the better training and education of psychologists performing custody evaluations. Guidelines are provided for the use of psychological tests in custody evaluations, while the limitations of the study, as well as directions for future research, are indicated. There is considerable debate concerning psychologists’ legitimacy and ability to adequately address the legal question in custody evaluations. Authors in favour of the ultimate opinion rule suggest that psychologists are acting beyond the scope of their scientific, professional and ethical expertise by providing ultimate issue recommendations. Authors against the ultimate opinion rule suggest that psychologists are acting within the scope of their abilities; that custody recommendations by psychologists in family law are a relevant necessity and the ultimate opinion rule places the court in a worse position to understand expert testimony. Some authors take a cautionary route, suggesting that only well-trained and experienced forensic evaluators should offer ultimate opinions, after taking into consideration all relevant data and scientific material. This study evaluated 24 psychologists’ recommendations in child custody reports performed for the Office of the Family Advocate. The psychologists’ recommendations were analysed to determine the frequency of ultimate issue recommendations and the extent to which these recommendations corresponded with the resulting court order. These psychologists followed the international trend and provided custody recommendations in the vast majority of the forensic reports, while there was 94% accordance between the psychologists’ ultimate issue recommendations and the final court order in stand-alone reports. However, concerns are expressed about the quality of the reports and the judiciary’s acceptance of such reports. A need for better training of psychologists performing custody evaluations and greater judicial vigilance is expressed. Indications for future research are given.
Thesis (Ph.D. (Psychology))--University of the Free State, 2012
Keywords: Child psychology; Custody of children; Children of divorced parents; Psychological tests in custody evaluations; Forensic assessment methodology; Child custody practice guidelines; Care and contact evaluations in divorce; Child custody evaluation; Child custody practice guidelines